DIFFUSE-WEIGHTED MAGNETIC RESONANCE IMAGING (DW-MRI) FOR CRYPTOGENIC STROKE DIAGNOSIS IN YOUNG ADULT FEMALE: A CASE REPORT - Lothar Matheus Manson Vanende Silalahi (Faculty of Medicine Universitas Kristen Duta Wacana, 2020)
Background: Ischaemic stroke is caused by various aetiology. Cryptogenic stroke diagnosis is established when no aetiologies are discovered although clinical manifestations are consistent with acute stroke. Diffusion-weighted magnetic resonance imaging (DW-MRI) is one neuroimaging modalities which could be useful in exploring aetiology instead of excluding intracranial haemorrhage. There are many conflicting pieces of evidence of the benefit using DW-MRI to confirm the presence or the absence of brain lesions. Objective: To report a clinical case of ischemic stroke with negative evaluation on advanced neuroimaging studies (DW-MRI). Case Description: A female, 35 years old, presented to the emergency unit with a 6 hours history of prickling sensation before admission. There were no risk factors of stroke, and no other neurological symptoms. The neurologic examination reveals left hemihypesthesia, with normal results on laboratory examination for stroke risk factors and negative ischemic lesion on brain DW-MRI. Explorative examination on cardiac aetiologies was negative. Patient was given a standard regimen for acute stroke management despite the negative results and established as a cryptogenic stroke case. Conclusion: Diagnosis of ischemic stroke should rely mainly on clinical findings, with consideration of cryptogenic stroke when there is no aetiology found after thorough examination. Nevertheless, comprehensive examination on cardiac function and coagulation tests should be performed whenever possible to determine the cause of ischaemic stroke.